Nilai Personal Dan Kesenjangan Anggaran - Sebuah Hubungan Kausalitas - Lisa Martiah Nila Puspita; Rifaatul Khoiriyah; Lukluk Fuada (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The study aimed to investigate individual values that involved in planning activities. This study tested the effect of three type of personal values (achievement, power, and tradition) on budgetary slack. This study used theory of planned behaviour. To determine the budgetary slack in this survey, 30 accounting students at Bengkulu University as respondents performed the specific task in December 2014. Firstly, they prepared a budget based on the real need, then the slack was created. Data was analysis by using multiple linear regression. The regression results indicated that the value of achievement and power values positively effected on budgetary slack. This meant that the higher the value of a person's achievement and power, the greater budgetary slack occurred. While the value of tradition negatively affected the budgetary slack, which means that the higher the value of tradition in the possession, the smaller the budgetary slack done. The limitation of this study was the measurement of the individual values obtained low result which indicated lack of correlation between the items in questionnaires. Therefore, the suggestion for future research is to improve or review the questionnaires that are used in this study.